Service intelligence and service science : evolutionary technologies and challenges - Leung, Ho-Fung.; Chiu, Dickson K. W., 1966-; Hung, Patrick C. K. (Information Science Reference, 2010)
"This book presents the emerging fields of service intelligence and service science, positioning them as the most promising directions for the evolution of service computing, demonstrating the critical role such areas play in supporting service computing processes"--Provided by publisher.